ÐœÐ¾Ð´Ð¸Ñ„Ð¸ÐºÐ°Ñ†Ð¸Ñ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ð¸ Ð¡Ð°2+-ÐÐ¢Ð Ð°Ð·Ñ‹ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð¿Ð¾Ð´ Ð²Ð»Ð¸ÑÐ½Ð¸ÐµÐ¼ Ð³Ð»Ð¸Ñ†ÐµÑ€Ð¾Ð»Ð°, Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸Ñ Ð¸ Ð² ÑÑ€ÐµÐ´Ð°Ñ… Ñ Ñ€Ð°Ð·Ð»Ð¸Ñ‡Ð½Ð¾Ð¹ Ð¸Ð¾Ð½Ð½Ð¾Ð¹ ÑÐ¸Ð»Ð¾Ð¹ - Zemlyanskikh, N. G.; Kofanova, O. A.; Babijchuk, L. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2005)
The change in erythrocytes’ Ca2+-ATPase activity in critical moments of cell life, including cryopreservation, can play an important role in preserving their structural and functional integrity. Endocellular cryoprotectant glycerol is capable to modify the Ca2+-ATPase activity by concentration-dependent way. Using the saponin-perforated cells as a model the low concentrations of glycerol were demonstrated to stimulate the Ca2+-ATPase-pump enzymatic activity, while the high ones inhibited the rate of ATPase reaction. An activating effect of glycerol in respect of Ca2+-ATPase can be related to both the involvement of its endogenous regulators and a modifying effect of medium parameters in controlling this ion-transporting system functional activity. The Ca2+-ATPase activity was noted to be changed under low temperature effect during erythrocyte preservation with glycerol protection, as well as a result of frozen-thawed cell deglycerolisation.